Pregnancy Changes the Response of the Vomeronasal and Olfactory Systems to Pups in Mice - Navarro-Moreno, Cinta; Sanchez-Catalan, Maria Jose; Barneo-Muñoz, Manuela; Goterris-Cerisuelo, Rafael; Belles, Maria; Lanuza, Enrique; Agustin-Pavon, Carmen; Martinez-Garcia, Fernando (Frontiers in Cellular Neuroscience, 2020)
Motherhood entails changes in behaviour with increased motivation for pups, induced in part by pregnancy hormones acting upon the brain. This work explores whether this alters sensory processing of pup-derived chemosignals. To do so, we analyse the expression of immediate early genes (IEGs) in the vomeronasal organ (VNO; Egr1) and centres of the olfactory and vomeronasal brain pathways (cFos) in virgin and late-pregnant females exposed to pups, as compared to buttons (socially neutral control). In pup-exposed females, we quantified diverse behaviours including pup retrieval, sniffing, pup-directed attack, nest building and time in nest or on nest, as well as time off nest. Pups induce Egr1 expression in the VNO of females, irrespective of their physiological condition, thus suggesting the existence of VNO-detected pup chemosignals. A similar situation is found in the accessory olfactory bulb (AOB) and posteromedial part of the medial bed nucleus of the stria terminalis (BSTMPM). By contrast, in the medial amygdala and posteromedial cortical amygdala (PMCo), responses to pups-vs-buttons are different in virgin and late-pregnant females, thus suggesting altered sensory processing during late pregnancy. The olfactory system also shows changes in sensory processing with pregnancy. In the main olfactory bulbs, as well as the anterior and posterior piriform cortex, buttons activate cFos expression in virgins more than in pregnant females. By contrast, in the anterior and especially posterior piriform cortex, pregnant females show more activation by pups than buttons. Correlation between IEGs expression and behaviour suggests the existence of two vomeronasal subsystems: one associated to pup care (with PMCo as its main centre) and another related to pup-directed aggression observed in some pregnant females (with the BSTMPM as the main nucleus). Our data also suggest a coactivation of the olfactory and vomeronasal systems during interaction with pups in pregnant females.